Total and differential leukocytes counts, but not hsCRP, ESR, and five fractioned serum proteins have significant potency to predict stable coronary artery disease - Rasouli, Mehdi; Kiasari, Asadollah Mohseni; Bagheri, Babak (Clinica chimica acta, 2007)
The role and diagnostic value of markers of inflammation is well recognized in acute coronary syndromes but it is uncertain in patients with stable coronary artery disease (CAD). This study was done to investigate the association of markers of inflammation with the occurrence and severity of CAD and to evaluate their predictive values. Markers of inflammation, electrophoresis serum protein fractions, serum (apo)lipoproteins and classical risk factors were determined in 270 angiographically documented subjects. The subjects were classified as CAD cases and controls according to angiography. The severity of CAD was scored on the basis of the number and extent of lesions. The counts of total leukocytes (7.14±1.86 cell/nl vs. 6.58±1.62, p≤0.02), neutrophils (3.95±1.42 vs. 3.59±1.07, p≤0.05) and eosinophils (0.25±0.28 vs. 0.19±0.24, p≤0.03) were increased significantly, whereas the concentrations of high-sensitivity C-reactive protein (hsCRP, 2.03 (0.0−32.0) mg/l vs.1.72 (0.09−11.36), p≤0.07) changed modestly in CAD patients relative to controls. There were no significant differences in the counts of monocytes and lymphocytes and the concentrations of erythrocyte sedimentation rate (ESR) and any five fractions of serum proteins between two groups. The counts of total leukocytes, neutrophils and eosinophils, but not hsCRP and ESR exhibited significant associations with the severity of CAD. In univariate logistic regression analysis, leukocytes count associated significantly (OR=1.97, p≤0.01) whereas hsCRP modestly (OR=1.76, p≤0.06) with the occurrence of CAD. The association was lessened by diabetes mellitus in multivariable adjustment. Receiver operating characteristic (ROC) analysis showed that, only total leukocyte and differential counts had significant potency to predict CAD (area under curve, AUC=0.60±0.04, p≤0.02). The total leukocytes count and its subgroups are associated with the presence and severity of CAD, but the associations were not independent. The efficiency was questioned for hsCRP, ESR and five fractioned serum proteins to identify stable CAD.